Characterisation of physiological conditions and evaluation of well-being in two species of bivalve molluscs (Ruditapes philippinarum and Chamelea gallina) intensively exploited in coastal and lagoon areas of the Northern Adriatic Sea (Italy) - Moschino, Vanessa (2011)
Tese de Doutoramento, Ecologia, Especialidade de Ecofisiologia, Faculdade de Ciências do Mar e do Ambiente, Universidade do Algarve, 2007